2006
DOI: 10.1097/01.olq.0000216032.52731.ea
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Syphilis Screening Among Women With Prenatal Care in a Community With a High Syphilis Incidence

Abstract: Few women were screened according to standard recommendations, and provider or institutional-related factors affected adequacy of screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
2
22
1
4
Order By: Relevance
“…Estudos realizados com puér-peras em outros locais também revelaram oportunidades perdidas na testagem para detecção da infecção pela sífilis e pelo HIV, 17,18,25,26 sendo o diagnóstico oportuno da sífilis na gravidez o principal desafio para o controle da sífilis congênita. 5,27 Alguns estudos atribuem a baixa realização dos exames a não adesão dos profissionais ao protocolo de testagem universal das gestantes, sendo observadas variações em sua realização conforme tipo de serviço, 19,28 região do país 16,25 e características demográficas, socioeconômicas e reprodutivas das gestantes, [16][17][18][19]28 revelando percepções diferenciadas da vulnerabilidade das mulheres às DST que resultariam em menor oferta do exame.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Estudos realizados com puér-peras em outros locais também revelaram oportunidades perdidas na testagem para detecção da infecção pela sífilis e pelo HIV, 17,18,25,26 sendo o diagnóstico oportuno da sífilis na gravidez o principal desafio para o controle da sífilis congênita. 5,27 Alguns estudos atribuem a baixa realização dos exames a não adesão dos profissionais ao protocolo de testagem universal das gestantes, sendo observadas variações em sua realização conforme tipo de serviço, 19,28 região do país 16,25 e características demográficas, socioeconômicas e reprodutivas das gestantes, [16][17][18][19]28 revelando percepções diferenciadas da vulnerabilidade das mulheres às DST que resultariam em menor oferta do exame.…”
Section: Discussionunclassified
“…Inadequação na solicitação do segundo VDRL foi também observada em estudo realizado em maternidades de referência no Brasil 26 e em regiões dos EUA com elevada prevalência de sífilis, onde o segundo exame é recomendado como parte da rotina de pré-natal. 16,20,28 A menor solicitação do segundo exame anti-HIV é possivelmente decorrente da implantação recente dessa rotina no município do Rio de Janeiro, ocorrida no mesmo período do início desta pesquisa.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…For example, in 2001 the state of Florida in the United States of America (USA) passed a law requiring that at least two syphilis tests be administered during pregnancy, but operational research from Miami showed that only 83% of pregnant women were screened at least once. 11 In a study from Mongolia, only 77% of 3519 pregnant women were screened and the presence of congenital syphilis showed an association with late-term antenatal care and with living farther from care services. 12 The influence of health systems issues on timely prenatal syphilis screening has been observed in several other countries, including Bolivia, Kenya and South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Close attention to CS rates in Arizona is needed due to the recent legislation that may adversely affect health care seeking behaviors among recently immigrated women of childbearing age. Additional study is needed to determine the prenatal syphilis screening practices of providers delivering care to pregnant women in Arizona and available PNC options for noncitizen women.…”
mentioning
confidence: 99%